Clinical features and outcome of typhoid fever and invasive non-typhoidal salmonellosis in a tertiary hospital in Belgium: analysis and review of the literature. Issue 4 (August 2015) - Yombi, J. C.; Martins, L.; Vandercam, B.; Rodriguez-Villalobos, H.; Robert, A.
Abstract : Objectives: Typhoid fever (TF) occurs rarely in industrialized countries because of advances in health care and improvement of drinking water. Conversely, non-typhoid salmonellosis (NTS) remains widespread, because of food contamination or asymptomatic carriage. Non-typhoid salmonellosis can be severe when becoming invasive non-typhoid salmonellosis (iNTS). Although established prognostic indicators of the two pathologies are different, direct comparisons between iNTS and TF in the literature remain scarce. The purpose of this study was to analyse and compare demographic, clinical features and outcome of hospitalized patients with TF and iNTS. Methods: Demographic, clinical features and outcome were retrospectively analysed in a series of patients hospitalized between 2007 and 2012. Results: A total of 33 patients were enrolled, including 13 with established TF and 20 with iNTS. No differences between TF and iNTS patients were observed in incidence of fever, abdominal cramps, diarrhoea, headache, nausea and vomiting and duration of antibiotic therapy ( ≤ 7 days in both groups). Although the clinical outcome of TF patients was identical to that of iNTS patients, including incidence of complications, length of hospitalization and mortality (1/13 (7.7%) vs 2/20 (10%), P = 0.43), comorbidities were less frequent in the TF group than in the iNTS group (2/13 vs 15/20, P = 0.003). Conclusion: The clinical profile and outcome of TF patients are similar to those with iNTS. Although comorbidities are more often associated with iNTS, the results of our study suggest that clinical management of these two diseases should remain similar.